The Experience of Ethnic Identi fi cation on Intermarriages of Koreans in Japan - Yem, N. B. (Journal of Oriental Studies, 2016)
Based on the theory of ethnic identification of the author in this paper has researched particularities of ethnicidenti fication of the Korean diaspora in Japan: the case of inter-ethnic marriages.